2014
DOI: 10.1002/2013jf002957
|View full text |Cite
|
Sign up to set email alerts
|

Finite amplitude bars in mixed bedrock-alluvial channels

Abstract: We present a nonlinear asymptotic theory of fully developed flow and bed topography in a wide channel of constant curvature to describe finite amplitude perturbations of bottom topography, subject to an inerodible bedrock layer. The flow field is evaluated at the leading order of approximation as a slowly varying sequence of locally uniform flows, slightly perturbed by a weak curvature-induced secondary flow. Using the constraint of constant fluid discharge and sediment flux, we calculate an analytical solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 47 publications
(84 reference statements)
4
50
0
Order By: Relevance
“…These results, which are summarized in Figure , are consistent with those of Nelson et al (), who studied point bar behavior in a mixed bedrock‐alluvial channel bend and found that decreasing sediment supply leads to narrower point bars. Their model, however, applies only to alluvial deformation of a fixed bed, and cannot handle vertical and lateral bedrock erosion associated with sediment transport.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results, which are summarized in Figure , are consistent with those of Nelson et al (), who studied point bar behavior in a mixed bedrock‐alluvial channel bend and found that decreasing sediment supply leads to narrower point bars. Their model, however, applies only to alluvial deformation of a fixed bed, and cannot handle vertical and lateral bedrock erosion associated with sediment transport.…”
Section: Discussionsupporting
confidence: 91%
“…the ratio k sb /k sa , has been observed to affect the areal fraction of alluvial cover (Chatanantavet and Parker, 2008;Inoue et al, 2014;Johnson, 2014) and the characteristics of alternate bars (Nelson and Seminara, 2012). In a curved bedrock channel, however, the influence of relative roughness on the characteristics of a point bar is small (Nelson et al, 2014). To simplify our simulations here, the hydraulic roughness height for bedrock k sb is taken to be equal to the hydraulic The abrasion coefficient for bedrock β is taken to be 0.025 m -1 in all the simulations.…”
Section: Numerical Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these effects help to increase the abrasion on the outer bank by moving sediment. Nelson et al (2014) and Inoue, Parker, and Stark (2017) calculated the shape and thickness of alluvial cover in a bend in a mixed bedrock-alluvial river. They showed that the height and width of the point bar increase with increasing sediment supply.…”
Section: 1029/2017jf004387mentioning
confidence: 99%
“…Field observations [ Hodge et al ., ], flume experiments [ Chatanantavet and Parker , ; Hodge et al ., ], and theoretical analyses [ Hodge et al ., ; Nelson and Seminara , ; Nelson et al ., ] have demonstrated that the most stable configuration of sediment on a bedrock surface is in patches, producing a spatial pattern of discrete alluvial and bedrock areas. Despite this, within‐reach‐scale patterns of sediment cover in bedrock‐alluvial rivers have not received significant attention.…”
Section: Background and Research Questionsmentioning
confidence: 99%